2011
DOI: 10.1116/1.3664765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating operating conditions for continuous atmospheric atomic layer deposition using a multiple slit gas source head

Abstract: Continuous atmospheric atomic layer deposition (ALD) is based on the separation of ALD reactants in space rather than in time. In this study, operating conditions for continuous atmospheric ALD were evaluated using a multiple slit gas source head. A test apparatus was constructed consisting of a gas source head that sits above a substrate that is driven by a programmable stepper motor. The gas source head was composed of a series of rectangular channels that spatially separate the ALD reactants. With Al2O3 ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In our experimentation, a constant growth rate of 0.98 Å per cycle was recorded, which means that one pass (five ALD cycles) would result in a film thickness of ∼4.9 Å. This achieved growth rate of 0.98 Å per cycle is slightly lower than in conventional ALD systems, but it is comparatively higher than other reported values of the latest ALD technologies . The study also demonstrated that the amount of Al 2 O 3 deposited during the starting cycles of ALD is virtually the same as in the later ALD cycles.…”
Section: Resultssupporting
confidence: 45%
See 2 more Smart Citations
“…In our experimentation, a constant growth rate of 0.98 Å per cycle was recorded, which means that one pass (five ALD cycles) would result in a film thickness of ∼4.9 Å. This achieved growth rate of 0.98 Å per cycle is slightly lower than in conventional ALD systems, but it is comparatively higher than other reported values of the latest ALD technologies . The study also demonstrated that the amount of Al 2 O 3 deposited during the starting cycles of ALD is virtually the same as in the later ALD cycles.…”
Section: Resultssupporting
confidence: 45%
“…Scientific studies have reported that the cycle time may be as long as many minutes and result in deposition of films with thickness of approximately one angstrom, which greatly reduces the efficiency of ALD technology . Apart from that, the conventional ALD is a vacuum‐based technology and has rarely been reported to be used for the fabrication of thin films under atmospheric pressure conditions . The size and design of the ALD reactor also affects the processing parameters of the ALD process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. SALD processes have been described by a number of authors, [9][10][11][12] and concepts for developing these into a roll-to-roll process have been proposed. [13][14][15] Previously, only one implementation has been constructed, which enables narrow webs to be coated in a roll-to-roll basis with a very restricted number of deposition cycles in one pass.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial ALD can be performed using a number of different designs based primarily on the gap between the gas source head and the substrate. 14 These designs include a translating gas source head or substrate moving horizontally back-and-forth with a gap of $30-100 lm defined either by mechanical separation or a gas bearing; [15][16][17] a substrate spinning underneath a gas source head with the gap of $20 lm defined by a gas bearing; 18 and a rotating cylinder design with the gap of $1 mm defined by two concentric cylinders. [19][20][21][22] Another design is based on a "serpentine" web moving through spatially separated reactants 23 or a "closed loop" flexible web moving under a gas source head.…”
Section: Introductionmentioning
confidence: 99%